Relationship between Teachers’ Professional Training and use of Instructional Strategies to Enhance Pupils’ Literacy Skills in Lower Primary Schools in Busia County, Kenya - Otwate Paul; Nyakwara Begi; Margaret Mwangi (Randwick International of Education and Linguistics Science Journal, 2021)
Children who possess adequate basic language skills develop cognitive and social skills required in life and workplace. It also enhances smooth transition, performance, and retention and completion rate. Teachers with adequate professional training skills exhibits a potential to influent development of language skills in children. The Kenyan policy states that basic education and early learning is compulsory to all children. Therefore, it is relevant that teachers are equipped with adequate training skills to become champions in the realization of the country’s overall goal in education sector. This paper presents results from a study conducted in lower primary schools in Nambale sub-county Busia County to establish whether teachers’ professional training had an influence in the way teachers use instructional strategies to enhance pupils’ literacy skills. This was essential towards improving overall academic outcomes and communications skills in children.